1995
DOI: 10.1007/bf02450036
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of culturable and non-culturable airborne fungi in a grain store in Delhi

Abstract: Fungal spores are important aeroallergens and proper knowledge of their qualitative and quantitative prevalence in indoor and outdoor environments is of paramount importance in the study of allergic disorders. The present investigation was aimed at the study of seasonal and annual prevalence of fungi inside a large grain storage facility. Sampling was carried out from September 1989 to August 1991. Although fungal spores occurred throughout the year there was seasonal variation. Aspergillus flavus, Cladosporiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…Aspergillus is widespread in the environment where they may colonize grains, leaves and soil. The predominance of Aspergillus and Penicillium is in agreement with Pandit, Singh and Singh (1995) who reported that Aspergillus, Penicillium, Cladosporium and smut were the dominant species in bakeries. Lugauskas, Krikstaponis, & Sveistyte (2004) found a variety of fungal types including: Cladosporium, Alternaria, Geotrichum, Oidiodendron, Rhizopus, Torula, Spegazzinia, Acremonium and Cochliobolus in grain mills.…”
Section: Discussionsupporting
confidence: 92%
“…Aspergillus is widespread in the environment where they may colonize grains, leaves and soil. The predominance of Aspergillus and Penicillium is in agreement with Pandit, Singh and Singh (1995) who reported that Aspergillus, Penicillium, Cladosporium and smut were the dominant species in bakeries. Lugauskas, Krikstaponis, & Sveistyte (2004) found a variety of fungal types including: Cladosporium, Alternaria, Geotrichum, Oidiodendron, Rhizopus, Torula, Spegazzinia, Acremonium and Cochliobolus in grain mills.…”
Section: Discussionsupporting
confidence: 92%
“…Aspergillus was also the most dominant fungal group in the present study. A similar result was also found by Singh et al 29 and Pandit et al 12 in Delhi, India. Khan et al , 30 from Kuwait have also found Aspergillus species to be the predominant component of the aerospora.…”
Section: Discussionsupporting
confidence: 88%
“…Among the 35 fungal genera isolated, the prevalent fungal groups from all of the homes were different species of Aspergillus , Penicillium , Alternaria , and Cladosporium. Nonsporing isolates and yeast were also frequently isolated but they were grouped into “others.” Some of these fungi have been reported as the most common airborne fungi in different environments in other studies also 12 , 23 , 26 – 30 and have been considered to be the potent allergens in aerospora of many indoor and outdoor environments contributing to the increase in respiratory diseases in children as well as adults. 31 – 33 Aspergillus was the most diverse genera in terms of number of species identified in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…The prevalent fungal groups from all the sampling sites were Cladosporium, non-sporing isolates, Alternaria, Pencillium and Asperigillus, some of which have been reported as the most common airborne fungi in different environments in other studies Pandit et al, 1995;Rosas et al, 1997;Waisel et al, 1997;Picco and Rodolfi, 2000;Shelton et al, 2002;Huang et al, 2002;Hargreaves et al, 2003;Kuder, 2003;Adhikari et al, 2004). Cladosporium, comprising more than one third of the collected samples, was the most dominant fungal group in the present study.…”
Section: Discussionmentioning
confidence: 57%
“…It was reported that the dominant fungi were Cladosporium, Alternaria, Penicillium, Aspergillus in the atmosphere (Pandit et al, 1995;Singh et al, 1995;Rosas et al, 1997;Waisel et al, 1997;Picco and Rodolfi, 2000;Huang et al, 2002;Shelton et al, 2002;Hargreaves et al, 2003;Kuder, 2003;Adhikari et al, 2004), and their concentrations differed from place to place because of local environmental variables, fungal substrates, and human activities (Banerjee et al, 1987;Li and Kendrick, 1994;Hameed and Khodr, 2001;Shelton et al, 2002). However, little is known about the species, number, and size distribution of airborne fungi in Beijing.…”
Section: Introductionmentioning
confidence: 99%